Optimized robust control for improving frequency response of delay dependent AC microgrid with uncertainties - Kumar, Arvind; Bhadu, Mahendra; Arabi, Amir Ibrahim Ali; Kamangar, Sarfarz; Bhutto, Javed Khan; Ali, Mohammed Azam; Kumar, Sunil (Electric power systems research, 2024)
•Optimization-based robust output feedback controller to stabilize the frequency of the interconnected AC microgrid.•Design process employs a mixed H2/H∞ robust control based on linear matrix inequality.•Proposes an improved frequency control, enabled by augmenting the conventional frequency control with a speedy-acting improved power stability control loop.•Improved power stability control loop incorporated with area disturbance identifier, demand response aggregators, and set point modulation.•Contains case studies on an AC microgrid system, including low inertia solar PV power and wind generation. Illustrates the impact of communication time delay, packet dropout, and parameter uncertainties. Converter-interface-based renewable energy incorporated into modern power systems causes deterioration in power system stability and it is proving to be a main challenge for operators using sluggish traditional generation with a growing share of converter-interface generation, and there is a need for an alternative means to deliver rapid frequency control. This paper proposes two control loops as secondary frequency control, first is an improved optimized delay-dependent frequency control to ensure robust frequency control under daily changes in system parameters that may occur in prospective, renewable-rich future AC microgrids. For a variety of operating conditions, the design process employs a mixed H2/H∞ robust control based on linear matrix inequality (LMI). In second, a speedy-acting improved power stability control loop is utilized as the proposed secondary frequency control, because demand response aggregators can be beneficial for frequency control. Robustness is evaluated against several perturbations and communication delay attacks through dynamic simulation and stability is evaluated by small-signal analysis. Different case studies subject to generation\load loss, multiple time delay and parameter uncertainties are demonstrated on an interconnected AC microgrid system to verify the performance of the proposed control technique.